2020
DOI: 10.3390/cells9051177
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria in Health and Diseases

Abstract: Mitochondria are subcellular organelles evolved by endosymbiosis of bacteria with eukaryotic cells characteristics. They are the main source of ATP in the cell and play a pivotal role in cell life and cell death. Mitochondria are engaged in the pathogenesis of human diseases and aging directly or indirectly through a broad range of signaling pathways. However, despite an increased interest in mitochondria over the past decades, the mechanisms of mitochondria-mediated cell/organ dysfunction in response to patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
76
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(78 citation statements)
references
References 27 publications
0
76
0
2
Order By: Relevance
“…It is, however, possible that the domain(s) regulating LETM1-CHE/KHE would influence the interaction of LETM1 with proteins such as BCS1L and hence the regulation of mitochondrial morphology and vice versa. Given the increasing importance of inter-organelle communications and signaling for integrated cellular function in health and disease ( Javadov et al, 2020 ), this aspect of LETM1-mediated signaling, in addition to its exchanger function needs further investigation.…”
Section: Perspectivementioning
confidence: 99%
“…It is, however, possible that the domain(s) regulating LETM1-CHE/KHE would influence the interaction of LETM1 with proteins such as BCS1L and hence the regulation of mitochondrial morphology and vice versa. Given the increasing importance of inter-organelle communications and signaling for integrated cellular function in health and disease ( Javadov et al, 2020 ), this aspect of LETM1-mediated signaling, in addition to its exchanger function needs further investigation.…”
Section: Perspectivementioning
confidence: 99%
“…Previous age-related research has identified several cellular pathways that are consistently found to be dysregulated during ageing and in age-related disease. Cell energy and metabolism, including mitochondrial dysfunction, is one of the top processes (31)(32)(33). Proteins such as clusterin, superoxide dismutase 1(SOD1), and apolipoprotein E have previously been found to be dysregulated in ageing (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…In trabecular bone we observed decline in several collagens and proteoglycans, which are major structural components of the ECM. Bone also displayed a very strong metabolic, mitochondrial signature that has been linked to many ageing processes (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria are small subcellular organelles that generate adenosine triphosphate (ATP) to power various cell functions in all eukaryotic cells [ 1 , 2 , 3 , 4 ]. Mitochondria also control homeostasis and redox signaling and regulate cell apoptosis and death [ 1 , 2 , 3 , 4 ]. An alkaline pH ≈ 8.0 is essential in mitochondria to sustain the proton motive potential during the synthesis of ATP [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%